Impact of exposure to workplace sexual harassment on wellbeing among Ghanaian nurses: The role of resilience and conflict resolution climate - Justice Mensah; Eric Nanteer-Oteng; Richfield Atinyo (Elsevier, 2024)
Workplace sexual harassment is a pervasive issue with profound consequences for individuals' psychological wellbeing. This study investigates the impact of exposure to sexual harassment on nurses' psychological wellbeing. The study further examines the role of resilience and conflict resolution climate in the exposure to sexual harassment - nurses' psychological wellbeing relationship. A sample of 343 employed individuals completed measures of sexual harassment experiences, psychological wellbeing, resilience, and conflict resolution climate. Results revealed that sexual harassment was significantly and negatively associated with psychological wellbeing. Additionally, resilience mediated the relationship between sexual harassment and psychological wellbeing. However, contrary to expectations, the conflict resolution climate did not moderate the relationship between sexual harassment and psychological wellbeing. The study contributes to the literature by providing insights into the mechanisms through which sexual harassment affects individuals' wellbeing and emphasizes the significance of resilience as a protective factor. Practical implications are discussed in terms of supporting individuals who experience sexual harassment and promoting healthier work environments.